Association Between High Perceived Stress Over Time and Incident Hypertension in Black Adults: Findings From the Jackson Heart Study. Issue 21 (5th November 2019) - Spruill, Tanya M.; Butler, Mark J.; Thomas, S. Justin; Tajeu, Gabriel S.; Kalinowski, Jolaade; Castañeda, Sheila F.; Langford, Aisha T.; Abdalla, Marwah; Blackshear, Chad; Allison, Matthew; Ogedegbe, Gbenga; Sims, Mario; et al.
Abstract : Background: Chronic psychological stress has been associated with hypertension, but few studies have examined this relationship in blacks. We examined the association between perceived stress levels assessed annually for up to 13 years and incident hypertension in the Jackson Heart Study, a community‐based cohort of blacks. Methods and Results: Analyses included 1829 participants without hypertension at baseline (Exam 1, 2000–2004). Incident hypertension was defined as blood pressure≥140/90 mm Hg or antihypertensive medication use at Exam 2 (2005–2008) or Exam 3 (2009–2012). Each follow‐up interval at risk of hypertension was categorized as low, moderate, or high perceived stress based on the number of annual assessments between exams in which participants reported "a lot" or "extreme" stress over the previous year (low, 0 high stress ratings; moderate, 1 high stress rating; high, ≥2 high stress ratings). During follow‐up (median, 7.0 years), hypertension incidence was 48.5%. Hypertension developed in 30.6% of intervals with low perceived stress, 34.6% of intervals with moderate perceived stress, and 38.2% of intervals with high perceived stress. Age‐, sex‐, and time‐adjusted risk ratios (95% CI) associated with moderate and high perceived stress versus low perceived stress were 1.19 (1.04–1.37) and 1.37 (1.20–1.57), respectively ( P trend<0.001). The association was present after adjustment for demographic, clinical, and behavioral factors and baseline stress ( P trend=0.001). Conclusions: In a community‐based cohort of blacks, higher perceived stress over time was associated with an increased risk of developing hypertension. Evaluating stress levels over time and intervening when high perceived stress is persistent may reduce hypertension risk.